Disorientation patterns of loggerhead sea turtle (Caretta caretta) hatchlings in Pinellas County, Florida, USA - Kerry L. McNally; Carly Oakley; Megan Davila; Sarah Farinelli (PLoS ONE, 2026)
The disorientation of loggerhead sea turtle ( Caretta caretta ) hatchlings, primarily caused by artificial lighting, poses a significant threat to their survival, as they rely on environmental cues to reach the ocean. In this study, we analyzed data from nesting surveys and disorientation reports to identify factors contributing to disorientation events, including position on the beach and spatial location. Between 2018 and 2023, 1048 nests successfully had hatchlings emerge, with 377 (36%) of these emergences resulting in disorientation events. Nests located in the upper portion of the beach were significantly less likely to result in disoriented hatchlings compared to the middle portion. Spatiotemporal analysis identified areas of hot and cold spots of disoriented hatchlings across different beaches in Pinellas County, Florida, USA, with significant spatial variations of disorientations across years, with 2022 having peaks in spatial clustering and 2021 and 2023 having no clustering. Moonlight was found to play a mitigating role, with significantly more disorientation events occurring on nights with lower moonlight exposure. These findings underscore the need for improved lighting regulations and beach management strategies, such as enhancing natural dunes and beach profiles to reduce artificial light exposure in Pinellas County.